The Downfall of the American Order? - Katzenstein, Peter J.; Kirshner, Jonathan (Cornell University Press, 2022)
The Downfall of the American Order? offers penetrating insight into the emerging global political economy at this moment of an increasingly chaotic world. For seventy-five years, the basic patterns of world politics and the contours of international economic activity took place in the shadow of American leadership and the institutions it designed-an order designed to avoid the horrors of previous eras, including, most poignantly, two world wars and the Great Depression. But all things must pass. The global financial crisis of 2008, the legacy of two long, losing wars, and the polarizing and tumultuous presidency of Donald Trump all suggest that global affairs have reached a turning point. The implications of this are profound. The contributors to this book cast their eyes back on the order that once was, and look ahead to what might follow. In dialogue with each other's appraisals and expectations, they differ in their assessments of the probable, ranging from a hollowed-out American primacy muddling through by default, to partial modifications of old institutions and practices at home and abroad, and to wholesale contestations and the search for new orders. Contributors: Rawi Abdelal, Sheri Berman, Mark Blyth, Francis J. Gavin, Peter A. Gourevitch, Ilene Grabel, Peter J. Katzenstein, Jonathan Kirshner, and John Gerard Ruggie